The projection of Mexico in Cuba: under the shadow of deceiving 1886 - 1910 (Tzintzun, Revista de Estudios Históricos, 2016)
In the last three decades the Porfirio Diaz regime has undergone a profound his-toriographical review. All the constructed ideas that deserved nuances have beenreviewed by historians and return to the sources. One such issue is the projectionof the country and the ruler Porfirio Diaz in the heyday and success of the dicta-torship. It was understood that the expressions of admiration that Diaz provokedid not deserve much weight. However, according to recent historiography thesemanifestations are explained in large part because of diplomatic networks thatstretched around the world leader in order to project an idea of nation and theworld recognition as a creator in the construction of modern Mexico. This projec-tion and the role of diplomats has been studied in relations with Europe and theUnited States, however, there are no studies on other regions, also important in thenational project of Porfirio Diaz. This paper studies how the Mexican governmentprojected in Cuba the Diaz’s image of the Mexican nation and how the diplomaticmachinery and other agents associated with the promotional campaign worked,all under the shadow of deceiving.
Keywords: Porfirio Diaz; national image; projection; Cuba